Effect of water salinity on the water retention curve of geosynthetic clay liners. Issue 6 (December 2018) - Lu, Yi; Abuel-Naga, Hossam; Leong, Eng-Choon; Bouazza, Abdelmalek; Lock, Peter
Abstract: The effect of water salinity on the water retention curve of geosynthetic clay liners (GCLs), under constant volume condition is examined. The results indicate that at a constant gravimetric moisture content the total suction increases as the salinity of the wetting liquid increases. Furthermore, the difference in total suction between the GCL hydrated by saline water and distilled water is greater than the difference in the osmotic potential of the wetting water. This behaviour is possibly caused by the matric suction being affected by the expected chemically induced pore size change of the bentonite component of the GCL.